Development and Evaluation of High-Performance Decorrelation Algorithms for the Nonalternating 3D Wavelet Transform. (17th May 2007) - Moyano-Ávila Moyano-Ávila, E. E.; Quiles Quiles, F. J. F. J.; Orozco-Barbosa Orozco-Barbosa, L. L.
Abstract : We introduce and evaluate the implementations of three parallel video-sequences decorrelation algorithms. The proposed algorithms are based on the nonalternating classic three-dimensional wavelet transform (3D-WT). The parallel implementations of the algorithms are developed and tested on a shared memory system, an SGI origin 3800 supercomputer making use of a message-passing paradigm. We evaluate and analyze the performance of the implementations in terms of the response time and speed-up factor by varying the number of processors and various video coding parameters. The key points enabling the development of highly efficient implementations rely on the partitioning of the video sequences into groups of frames and a workload distribution strategy supplemented by the use of parallel I/O primitives, for better exploiting the inherent features of the application and computing platform. We also evaluate the effectiveness of our algorithms in terms of the first-order entropy.